2020
DOI: 10.1002/lt.25899
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Use of Normothermic Regional and Ex Situ Machine Perfusion in Donation After Circulatory Death Liver Transplant

Abstract: In Italy, 20 minutes of a continuous flat line on an electrocardiogram are required for declaration of death. In the setting of donation after circulatory death (DCD), prolonged warm ischemia time prompted the introduction of abdominal normothermic regional perfusion (NRP) followed by postprocurement ex situ machine perfusion (MP). This is a retrospective review of DCD liver transplantations (LTs) performed at 2 centers using sequential NRP and ex situ MP. From January 2018 to April 2019, 34 DCD donors were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 41 publications
2
83
0
Order By: Relevance
“…In this section, the most frequently used definitions are summarized. For DCD, we refer to the following terminology discussed during the Sixth International Conference on Organ Donation After Circulatory Death ( 30 ) and in the article by Ghinolfi and colleagues ( 13 ) :…”
Section: Methodsmentioning
confidence: 99%
“…In this section, the most frequently used definitions are summarized. For DCD, we refer to the following terminology discussed during the Sixth International Conference on Organ Donation After Circulatory Death ( 30 ) and in the article by Ghinolfi and colleagues ( 13 ) :…”
Section: Methodsmentioning
confidence: 99%
“…NMP provides an effective method for salvaging ECD organs. Davide et al retrospectively studied 34 transplantations of DCD donors using NMP and showed that it would be feasible for DCD LT ( 13 ). The prospective clinical trial of Otto et al reported that NMP was a safe option for risky donor livers and increased the number of available donor livers ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such marginal cDCD liver grafts may benefit from additional ex-vivo perfusion after NRP. Several Italian teams have proposed a sequential strategy with NRP followed by hypothermic oxygenated perfusion (HOPE) to rescue marginal cDCD liver and kidney grafts with FDWI up to 52.5 min for livers and 325 min for kidneys [30][31][32]. In the absence of validated biomarkers during NRP and following the positive results of two recent randomized trials on HOPE in cDCD liver and kidney transplantation, we suggest adding a period of HOPE after NRP in highrisk grafts to assess mitochondrial viability prior to implantation [12,24,[33][34][35][36].…”
Section: Based On Macroscopic Aspect ‡mentioning
confidence: 99%